АНТИОКСИДАНТНАЯ СИСТЕМА ОРГАНИЗМА ПРИ ГИПОТИРЕОЗЕ И РТУТНОЙ ИНТОКСИКАЦИИ (Experimental biology, 2009)
In the article was studied influence of the hypothyroidism and mercury on the activity of next antioxidant system enzymes: superoxidedismutase (SOD), glutationperoxidase (GPO), glutatioreductase (GR) in the sensitive organs, tissues of liver, kidneys and serum of blood. Results of showed about series changes of the antioxidant system enzymes in thehypothyroidism and mercury intoxication.
Keywords: hypothyroidism; superoxidedismutase (SOD)